Pengaruh Model Pembelajaran Kooperatif Dan Sikap Ilmiah Terhadap Hasil Belajar Matematika Dengan Mengontrol Inteligensi - Pesik, Anneke (SOSCIED, 2024)
The purpose of this study was to empirically investigate the effect of cooperative learning model and scientific attitude on mathematics learning outcomes, after controlling for intelligence. The research method used was experimental method with treatment by level 2x2 design. To test the hypothesis, the data were analyzed by analysis of covariance. The results obtained after controlling for intelligence: (1) mathematics learning outcomes in the group of students taught with TGT type cooperative learning model is higher than the group of students taught with Scramble type cooperative learning model, (2) there is an interaction effect of learning model with scientific attitude on students' mathematics learning outcomes, (3) for students who have positive scientific attitude, (3) for students who have positive scientific attitude, mathematics learning outcomes in the group taught with TGT type cooperative learning model are higher than the group taught with Scramble type cooperative learning model, and (4) for students who have negative scientific attitude, mathematics learning outcomes in the group taught with TGT type cooperative learning model are lower than the group taught with Scramble type cooperative learning model. In teaching, teachers must be creative in using learning models in order to create an effective learning atmosphere and can improve mathematics learning outcomes optimally.